Beyond containment: Health systems responses to COVID-19 in the OECD (OECD Policy Responses to Coronavirus (COVID-19), 2020)
Health systems are facing the most serious global pandemic crisis in a century. The main focus of this brief is on the policies aimed at providing effective care and managing the pressure on health systems